2020
DOI: 10.5546/aap.2020.eng.56
|View full text |Cite
|
Sign up to set email alerts
|

H-type tracheoesophageal fistula in neonatal period: Difficulties in diagnosis and different treatment approaches. A case series

Abstract: Congenital tracheoesophageal fistula not associated with esophageal atresia, known as H-type fistula, is an uncommon anomaly. It presents with cough, choking, and cyanosis during feeding and/or recurrent pneumonia. Although symptoms are usually present from birth, diagnosis is difficult. The rarity of this disease, non-specific symptoms, and the limitations of radiological and endoscopic confirmation of the fistula often result in a delay between presentation and diagnosis confirmation. Here we describe the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have shown that salivagram is often used in the diagnosis and treatment of congenital oesophageal atresia, tracheo-oesophageal fistula, and aspiration pneumonia in children (19)(20)(21)(22). From these reports, we can also infer that salivagram is a safer method of inspection.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that salivagram is often used in the diagnosis and treatment of congenital oesophageal atresia, tracheo-oesophageal fistula, and aspiration pneumonia in children (19)(20)(21)(22). From these reports, we can also infer that salivagram is a safer method of inspection.…”
Section: Discussionmentioning
confidence: 85%
“…To improve sensitivity, this test should be performed with a nasogastric tube in situ and the child should be in the prone position. [6] The nasogastric tube should be withdrawn slowly while injecting contrast. Contrast-enhanced studies carry a risk of aspiration pneumonia and should be performed with adequate emergency resuscitation tools at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Although some H-type variations of EA have been described previously [ 7 ], to our knowledge, the presence of an H-type congenital tracheo-oesophageal fistula associated with oesophageal stenosis in a neonate has yet to be reported in the literature. Thus, surgeons treating patients with suspected EA must be aware of this variant.…”
Section: Discussionmentioning
confidence: 99%